Numerical Investigation on Effects of Step Number on the Stepped Solar Still - Huynh, Huỳnh Văn Nam; Dang, Đặng Văn Hải; Nguyen, Nguyễn Minh Phú (Journal of Technical Education Science, 2024)
The stepped solar still is a modification of the traditional form to increase productivity by reducing the distance between the heat transfer and mass transfer surfaces. In this paper, two-dimensional numerical simulations of a traditional distiller and step-distillers are presented. The number of steps varies from 2 to 4 while the still dimensions and surface temperatures are the same. The study was to determine the transport characteristics in the evaporative domain and the freshwater yield rate of the stepped types compared with the traditional type. The results show that the optimal number of steps is 3, and the yield of this type is 19.7% higher than that of the traditional one. The productivity of the stepped types is higher than that of the traditional type because the number of primary vortexes is increased from 3 to 5. In addition, the different number of vortexes in a step of the stepped distillers also results in different productivity of the step. The strong secondary vortices at the water and glass surfaces of the conventional type prevent heat and mass transfer.